Cicero in the Encyclopaedia of Giorgio Valla - Amedeo Raschieri (Ciceroniana On Line)
Cicero has been a fundamental reference point for school education and the system of artes liberales, especially for rhetoric and philosophy, from ancient times to the Renaissance. I intend to focus my attention on the Venetian environment in the second half of the 15th century and, in particular, on Giorgio Valla. This humanist was trained in the Milanese area but carried out his teaching activity in Venice for an extended period. He distinguished himself through his literary and scientific interests, but, above all, through his encyclopaedic conception of knowledge. First, I provide some details about Giorgio Valla’s life, his activity as a translator and publisher of Greek scientific works, and his library. Second, I analyse his interest in Cicero and Greek rhetoric, and his commentaries on Cicero’s works: De fato, Topica, Timaeus, Rhetorica ad Herennium (which, according to Valla, was a work of Cicero), Partitiones oratoriae, and Tusculanae disputationes. Finally, I present Valla’s posthumous encyclopaedia, the De expetendis ac fugiendis rebus, and, in particular, Cicero’s presence in its books on rhetoric.